2013
DOI: 10.1186/1472-6963-13-23
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence and ingredient cost of chronic comorbidity in the Irish elderly population with medication treated type 2 diabetes: A retrospective cross-sectional study using a national pharmacy claims database

Abstract: BackgroundComorbidity in patients with diabetes is associated with poorer health and increased cost. The aim of this study was to investigate the prevalence and ingredient cost of comorbidity in patients ≥ 65 years with and without medication treated type 2 diabetes using a national pharmacy claims database.MethodsThe Irish Health Service Executive Primary Care Reimbursement Service pharmacy claims database, which includes all prescribing to individuals covered by the General Medical Services scheme, was used … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
46
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(50 citation statements)
references
References 42 publications
4
46
0
Order By: Relevance
“…The proportion of patients with coexisting diabetes and hypertension in our study was higher than that reported by EMR‐based studies in other countries. An analysis of ambulatory adult T2DM patients in a center in the United States demonstrated a prevalence of 17.8%, while a study in Ireland found 32.2% T2DM patients on antihypertension therapy . This diversion might be a consequence of the heterogeneity of patients’ characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The proportion of patients with coexisting diabetes and hypertension in our study was higher than that reported by EMR‐based studies in other countries. An analysis of ambulatory adult T2DM patients in a center in the United States demonstrated a prevalence of 17.8%, while a study in Ireland found 32.2% T2DM patients on antihypertension therapy . This diversion might be a consequence of the heterogeneity of patients’ characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Regional data from Ireland have shown that the prevalence of diagnosed Type 2 diabetes among middle‐aged primary care patients ranged from 2.8% in 1998 to 5% in 2010–2011 . Cross‐sectional analysis of a national prescription database demonstrated a higher prevalence (9.1%) among adults aged over 65 years in 2010 . Type 2 diabetes is a significant cause of blindness, non‐traumatic lower limb amputations, end‐stage renal disease and cardiovascular disease .…”
Section: Introductionmentioning
confidence: 99%
“…Similar to other countries, Ireland does not have a national diabetes register or universal data‐capture system to monitor the burden of Type 2 diabetes and related complications. Prevalence estimates rely on data from observational studies . However, these estimates can vary due to differences in age ranges, study populations and case finding methods; comparability between studies is limited, making it difficult to observe trends over time .…”
Section: Introductionmentioning
confidence: 99%
“…However, epidemiological data on the medical and economic burden are very scarce and in absence of valid population‐based clinical data on migraine, healthcare claims data provide a valuable source for (pharmaco‐)epidemiological research . These data are reliable, longitudinal, comprise a large number of residents, can be seen as representative to the general population, and are widely used in epidemiological research to determine the prevalence of chronic diseases . Second, our cost estimates are not able to reflect the total cost‐of‐illness since data on indirect costs such as productivity losses due to work absenteeism were not available.…”
Section: Discussionmentioning
confidence: 99%
“…However, since all prescription drug items are coded and assigned to a respective ATC code in our database, we were thus able to assign certain ATC codes to different chronic diseases. In administrative databases, this mapping approach allows us a direct measure of treated diseases, and represents in the meanwhile a commonly used and reliable method to identify patients with chronic diseases . Furthermore, these drugs include the drug groups which were most frequently prescribed in primary care in Switzerland and, therefore, were likely to cover the majority of relevant drugs prescribed in real‐life patients .…”
Section: Methodsmentioning
confidence: 99%